Nilai Profetik dalam Pembelajaran Akidah Akhlak dan Kegiatan Ekstrakurikuler Pramuka di MAN Insan Cendekia Gorontalo - Budi Yahya Haeruddin; Said Subhan Posangi (Pascasarjana IAIN Sultan Amai Gorontalo, 2019)
This paper aims to reveal the prophetic values ​​in the learning of the Morals and in the extracurricular scout activities in MAN Insan Scholar Gorontalo. The method used is qualitative with a content analysis approach. The results of the study revealed that learning carried out in the classroom contained teaching activities carried out by educators. In this case the teaching method of the Prophet Muhammad became the role of the model for the implementation of the method of teaching the moral code, namely shiddiq, amanah, tabligh, and philosophy is a strong foundation in creating the learning of moral behavior which is expected in forming the noble person of the nation. Prophetic value in scout extracurricular activities. The prophetic values ​​contained in Dasadharma are clear evidence that MAN Insan Gorontalo Scholars through scouting activities must maintain their spirits so that they become superior madrasas in IPTEK and IMTAK.